Two new species and faunistic records of the genus Mannerheimia Mäklin, 1880 from India, Nepal and China, and additional notes on some eastern Palaearctic species of Omaliinae Macleay, 1825 (Coleoptera: Staphylinidae) - Shavrin, Alexey V. (Zootaxa, 2023)
New taxonomic and faunistic data for four species of the genus Mannerheimia Mäklin, 1880 from India, Nepal and China are provided. Two new species from the Himalayan Region are described and illustrated: M. prolongata sp.n. (India, Uttarakhand) and M. punctatissima sp.n. (Eastern Nepal, Taplejung). The distribution map for both new species is given. Faunistic and diagnostic data for several species of Omaliinae Macleay, 1825 from the Eastern Palaearctic Region are also given. New diagnostic data for Acrolocha rogeri Shavrin, 2017 and Amphichroum telnovi Shavrin, 2021 are provided. Depositories of the type material for three species of the genus Anthobium Leach, 1819 are clarified. The modified distributional maps for Amphichroum pindarense Champion, 1920, A. telnovi and A. anthobioides Champion, 1925 are provided. Several species are recorded from the certain area for the first time: Acidota crenata (Fabricius, 1792) from Kyrgyzstan, Acrulia inflata (Gyllenhal, 1813) from Maritime Province of Russia, Amphichroum pindarense from Nepal, A. telnovi from India, and M. hartmanni Shavrin, 2018 from the eastern part of Nepal (Solukhumbu).